Breast cancer pathology services in sub-Saharan Africa: a survey within population-based cancer registries - Hannes-Viktor Ziegenhorn; Kirstin Grosse Frie; Ima-Obong Ekanem; Godwin Ebughe; Bakarou Kamate; Cheick Traore; Charles Dzamalala; Olufemi Ogunbiyi; Festus Igbinoba; Biying Liu; Marcus Bauer; Christoph Thomssen; et al. (BMC, 2020)
Abstract Background Pathologists face major challenges in breast cancer diagnostics in sub-Saharan Africa (SSA). The major problems identified as impairing the quality of pathology reports are shortcomings of equipment, organization and insufficiently qualified personnel. In addition, in the context of breast cancer, immunohistochemistry (IHC) needs to be available for the evaluation of biomarkers. In the study presented, we aim to describe the current state of breast cancer pathology in order to highlight the unmet needs. Methods We obtained information on breast cancer pathology services within population-based cancer registries in SSA. A survey of 20 participating pathology centres was carried out. These centres represent large, rather well-equipped pathologies. The data obtained were related to the known population and breast cancer incidence of the registry areas. Results The responding pathologists served populations of between 30,000 and 1.8 million and the centres surveyed dealt with 10-386 breast cancer cases per year. Time to fixation and formalin fixation time varied from overnight to more than 72 h. Only five centres processed core needle biopsies as a daily routine. Technical problems were common, with 14 centres reporting temporary power outages and 18 centres claiming to own faulty equipment with no access to technical support. Only half of the centres carried out IHC in their own laboratory. For three centres, IHC was only accessible outside of the country and one centre could not obtain any IHC results. A tumour board was established in 13 centres. Conclusions We conclude that breast cancer pathology services ensuring state-of-the-art therapy are only available in a small fraction of centres in SSA. To overcome these limitations, many of the centres require larger numbers of experienced pathologists and technical staff. Furthermore, equipment maintenance, standardization of processing guidelines and establishment of an IHC service are needed to comply with international standards of breast cancer pathology.